Angle κ and its effect on the corneal elevation maps in refractive surgery candidates. Issue 10 (October 2022) - Salouti, Ramin; Nowroozzadeh, M. Hossein; Azizi, Ali; Salouti, Kia; Ghoreyshi, Maryam; Oboodi, Reza; Tajbakhsh, Zahra
Abstract : A large angle κ is independently associated with a greater corneal elevation value at the temporal quadrant for both front and back topographic maps. Abstract : Purpose: To assess the associations of angle κ and Pentacam decentration indices with elevation maps in normal refractive surgery candidates. Setting: Salouti Cornea Research Center, Salouti Eye Clinic, Shiraz, Iran. Design: Retrospective observational study. Methods: In this research, the right eyes of 173 refractive surgery candidates were assessed. Data of front and back corneal elevation maps, keratometric data, decentration indices, and corneal astigmatism obtained by Pentacam HR system and angle κ obtained by Orbscan IIz were extracted. Maximum elevation (or depression) for each of the 4 quadrants was recorded. Correlations of elevation values with angle κ, Pentacam decentration indices, keratometry, and astigmatism were examined by Pearson correlation coefficient. 148 age- and sex-matched cases with keratoconus grade 1 were selected as a positive control group, and Pentacam variables were compared between the groups. Results: Overall, data from 173 eyes of 173 normal refractive surgery candidates and 148 eyes of 148 patients with keratoconus were recorded and analyzed. In normal refractive surgery candidates, the mean of angle κ was 5.32 ± 1.36 (SD) degrees. Angle κ had a positive correlation with front and back temporal elevations based on a best-fit sphere (BFS) ( r = 0.339, P = .001; r = 0.300, P < .001, respectively). Front and back keratometric astigmatisms were positively correlated with front and back nasal and temporal elevations ( r ≥ 0.543, P < .001) and negatively correlated with superior and inferior elevations ( r ≤ −0.547, P < .001). These associations no longer existed when using best-fit toric ellipse (BFTE) for calculating elevation data. The thinnest point to vertex decentration was significantly associated with the back temporal elevation (based on the BFTE) in both normal ( r = 0.311, P < .001) and keratoconus ( r = 0.190, P = .021) eyes. Conclusions: This study showed that elevation maps obtained by the Pentacam system using BFS might be affected by both the large angle κ and corneal astigmatism, confounding the preoperative assessment of refractive surgery candidates. Using BFTE as a reference for calculating elevation data should eliminate most diagnostic issues and thus is encouraged in this context.